Unusual extrapulmonary manifestations of covert COVID-19: a case series at a tertiary care hospital in Bali, Indonesia - Ida Bagus Suparyatha; Dyah Kanya Wati; I Nyoman Budi Hartawan; Vanessa Lini Gunawan; Andreas Dhymas Dhyna Martha Kelana; Ivy Cerelia Valerie (Hygeia Press di Corridori Marinella, 2021)
One of the most challenging issues in facing the Coronavirus Disease (COVID-19) pandemic relies on the considerable uncertainty of the extent of its involvement. The wide spectrum of manifestations, ranging from generally milder manifestations to Multisystem Inflammatory Syndrome, and the concurrence with other disease entities substantially obscure clinical diagnosis. Diagnostic pitfalls persisted despite advancement in diagnostic criteria and modalities. We present a case series of confirmed COVID-19 cases in a tertiary hospital in Bali, Indonesia, with fever as the sole presenting feature and diagnostic hint.